2019
DOI: 10.1021/acs.organomet.9b00578
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Assisted Volatilization and Thermal Stability of Bis(imido)dichloromolybdenum(VI) ([(t-BuN═)2MoCl2]2) and Its Adducts

Abstract: Volatile molybdenum containing compounds have successfully been utilized for the atomic layer deposition of MoNx, MoO3, MoS2, and MoCxNy. Most of the reported volatile molybdenum containing compounds have been prepared via salt metathesis reactions of bis(tert-butylimido)dichloromolybdenum(VI), with anionic nitrogen based ligands. Herein we describe the preparation of several adducts of [(t-BuN=)2MoCl2]2 (2) via ligand exchange reactions with various neutral ligands, including both mono-and bidentate ethers, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(103 citation statements)
references
References 68 publications
4
97
0
2
Order By: Relevance
“…We applied our recently developed "Figure of merit" s that takes key parameters such as thermal range, vapor pressure, and extent of decomposition during TGA into account to quantitatively compare precursors (Table S2). [21,24] A positive (s = À2) where the weak performance of the latter originates from its low volatility. Therefore, 1 was not only competitive with successfully applied Co II precursors but, to the best of our knowledge, represents the only known potential Co IV precursor candidate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied our recently developed "Figure of merit" s that takes key parameters such as thermal range, vapor pressure, and extent of decomposition during TGA into account to quantitatively compare precursors (Table S2). [21,24] A positive (s = À2) where the weak performance of the latter originates from its low volatility. Therefore, 1 was not only competitive with successfully applied Co II precursors but, to the best of our knowledge, represents the only known potential Co IV precursor candidate.…”
Section: Methodsmentioning
confidence: 99%
“…To contextualize the performance of 1, we subjected two recently reported Co II precursors to thermal analysis: namely CoCl 2 (TMEDA) and Co(DAD) 2 (DAD= tert ‐butyldiazadienyl) (see the Supporting Inforamtion). We applied our recently developed “Figure of merit” σ that takes key parameters such as thermal range, vapor pressure, and extent of decomposition during TGA into account to quantitatively compare precursors (Table S2) . A positive Figure of merit indicates the suitability of a precursor while negative indicates a poor candidate.…”
Section: Figurementioning
confidence: 99%
“…Wir nutzten unser kürzlich entwickeltes "Gütemaß" s, das Schlüsselparameter wie den Nutzbereich, den Dampfdruck und das Ausmaß an Zersetzung während einer TGA für einen quantitativen Vergleich berücksichtigt (Tabelle S2). [21,24] Ein positiver Wert impliziert die Eignung einer Vorstufe, ein negativer das Gegenteil. Mit s = 35 ordnet sich 1 zwischen [Co(DAD) 2 ] (s = 64) und [CoCl 2 (TMEDA)] ein (s = À2), wobei das schlechte Resultat des Letztgenannten auf seiner geringen Flüchtigkeit beruht.…”
Section: Angewandte Chemieunclassified
“…Um die Kennzahlen von 1 in einen geeigneten Kontext zu setzen, unterzogen wir zwei jüngst publizierte Co II ‐Vorstufen derselben Analyse: CoCl 2 (TMEDA) und Co(DAD) 2 (DAD= tert ‐Butyldiazadienyl; siehe Hintergrundinformationen). Wir nutzten unser kürzlich entwickeltes “Gütemaß” σ , das Schlüsselparameter wie den Nutzbereich, den Dampfdruck und das Ausmaß an Zersetzung während einer TGA für einen quantitativen Vergleich berücksichtigt (Tabelle S2) . Ein positiver Wert impliziert die Eignung einer Vorstufe, ein negativer das Gegenteil.…”
Section: Figureunclassified
“…For example, a published assessment of a family of Mo compounds has found that one compound left a residue containing both MoClx and MoNx type species. 2 In cases like this the maximum residual mass could be chosen based on prior data about how the precursor might decompose, or the weighting factor might be set to (1 − %𝑚 𝑟𝑒𝑠 100% ), where mres is the measured residual mass from TGA. This more general term does not require any prior knowledge of the decomposition products.…”
Section: Introductionmentioning
confidence: 99%